New data on morphology and taxonomy of some species of the genus Nicrophorus Fabricius, 1775 (Coleoptera: Silphidae) - E.A. Khatchikov; D.S. Popov (Кавказский энтомологический бюллетень, 2006)
Descriptions of the endophallus (for 10 species) and female genital segments and genitalia (for 8 species) of the genus Nicrophorus Fabricius, 1775 are presented in the paper. Figures of described structures are given. A status of N. investigator interruptus stat. n. is lowered to subspecies level, N. tennuipes (Lewis, 1887) is included in the subgenus Nicrophorus Fabricius, 1775. Status of the following taxa is restored: subgenera Acanthopsilus Portevin, 1914 stat. resurr., Neonicrophorus Hatch, 1946 stat. resurr., Necrocleptes Semenov, 1933 stat. resurr., Nicrophorus Fabricius, 1775 stat. resurr., and subspecies Nicrophorus germanicus morio (Gebler, 1817) stat. resurr., N. germanicus fascifer (Reitter, 1884) stat. resurr.